Metode Analytical Hierarchy Process (AHP) untuk Pemilihan Media Sosial Pemasaran Songket Sambas - Wawan Setiawan; Alda Cendekia Siregar; Asrul Abdullah (JUSIFO : Jurnal Sistem Informasi, 2021)
Songket Sambas (Kain Lunggi) is a gold thread cloth typical of the culture of the Sambas people. The Sambas songket craftsmen have used social media a lot in marketing their products. The selection of the right social media in product marketing can help increase sales of Sambas songket. It can be the key to success in expanding Sambas songket sales to various regions. This study aims to apply the Analytical Hierarchy Process (AHP) method in the selection of social media that is widely used as the right Sambas songket marketing media. In this study, the AHP method was used as a method for decision making. In determining the pairwise comparison matrix, Sambas songket craftsmen were involved. The criteria used are age range (C1), gender (C2), number of users (C3), level of popularity (C4). From this study, we have the value of Facebook is 0.82, Instagram is 0.60, Youtube is 0.06, Twitter is 0.04. The final priority result of the right social media to use with the first order is Facebook.